Exploiting temperature windows: Temperature-dependent sensing mechanism for the selective detection of H2, CO, and NH3 - Gu, Junwen; Qian, Feng; Wang, Chao; Wang, Jie; Bao, Xiong; Yun, Di; Zhong, Xiang; Zhang, Cheng; Tao, ZeMin; Feng, Tan; Alho, Timo M.R.; Anarbaev, Maksatbek; et al. (Elsevier, 2026)
Addressing challenges in hydrogen safety monitoring and complex background gas interference, this study investigates a ZnFe2O4-based mixed-potential sensor for detecting H2, CO, and NH3. The sensor achieves a H2 sensitivity of 134.5 mV/decade at 400 °C with a 10 s response time and a 12 s recovery time at 500 °C, far exceeding the values for CO and NH3. Temperature governs gas diffusion, surface adsorption, and interfacial reaction kinetics, producing distinct optimal temperature windows for each target gas. Quantitative analysis of diffusion coefficients, adsorption enthalpy, and apparent activation energy reveals that molecular properties of size, bond energy, and polarity dictate the temperature-dependent selectivity. By regulating the operating temperature, the sensor exhibits selectivity coefficients of 0.1 for CO and 0.02 for NH3 relative to H2, remaining below 0.3 in mixed atmospheres. This temperature-window strategy offers a general design rationale for developing high-performance hydrogen sensors tailored for practical multi-gas environments.
Keywords: Mixed potential hydrogen sensor; Selectivity enhancement; Temperature dependence; Temperature modulation; Mechanism investigation; NH3-TPD; fi=Sähkötekniikka|en=Electrical Engineering|